2000
DOI: 10.1159/000029479
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and Laparotomic Cholecystectomy: A Randomized Trial Comparing Postoperative Respiratory Function

Abstract: Background: The fact that pulmonary complications occur in 20–60% of the patients subjected to abdominal operations clearly indicates that the lungs are the most endangered organ during the postoperative period. Objective: The aim of this study was to demonstrate the impact of cholecystectomy on postoperative respiratory disturbances by comparing the laparotomic cholecystectomy with laparoscopic gallbladder removal. Patients and Methods: A hundred cholecystectomized patients were included in the prospective ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
15

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 15 publications
1
35
0
15
Order By: Relevance
“…Essas alterações são descritas tanto em cirurgias por laparotomia quanto por videolaparoscopia, sendo menos acentuadas neste último tipo [8][9][10] . No entanto, ainda não está bem definido se a cirurgia videolaparoscópica reduz a incidência de CPP 1,2 .…”
Section: Introductionunclassified
“…Essas alterações são descritas tanto em cirurgias por laparotomia quanto por videolaparoscopia, sendo menos acentuadas neste último tipo [8][9][10] . No entanto, ainda não está bem definido se a cirurgia videolaparoscópica reduz a incidência de CPP 1,2 .…”
Section: Introductionunclassified
“…[6][7][8][9][10][23][24][25][26][27][28][29][30] Contudo, ainda não está totalmente esclarecido se um destes procedimentos cirúrgicos interfere mais do que o outro na mobilidade diafragmática e toracoabdominal do indivíduo.…”
Section: Discussionunclassified
“…6 Entretanto, alguns estudos mostraram que a manipulação da cavidade abdominal tanto na colecistectomia por laparotomia quanto na videolaparoscopia leva à diminuição significativa dos volumes e capacidades pulmonares nas primeiras horas de pós-operatório. [7][8][9][10] Isso ocorre possivelmente devido as duas formas cirúrgicas promoverem inibição reflexa do nervo frênico, com consequente disfunção diafragmática, afetando assim a ventilação e a expansão pulmonar. [11][12][13][14][15] Em 2008, Keus et al 9 compararam pacientes submetidos às duas formas de cirurgia e concluíram não existirem diferenças na função pulmonar dos pacientes em relação à técnica utilizada.…”
unclassified
“…(High quality evidence). LC seems a relatively safe procedure for special groups of patients such as the elderly, pregnant women or patients with cirrhosis and portal hypertension Child A y B (Low quality evidence) (ANDEM, 1994;Downs, 1996;Korolija, 2004;Mimica, 2000;Ros, Clinical High quality: it is very unlikely that future studies change our confidence in the estimate of effect and therefore our confidence is high. Moderate quality: it is likely that future studies change our confidence in the estimate of effect.…”
Section: Discussionmentioning
confidence: 99%
“…Four SRs (ANDEM, 1994;Downs, 1996;Korolija, 2004;Keus, 2006a;Keus, 2006b), two RCTs (Mimica, 2000;Ros, 2001), three cohort studies (Devereaux, 2005;Elder, 1996;Finan, 2006), one CPG (Zacks, 2002), one cross-sectional study (Collet, 1997) and one case series (Ibrahim, 2006) were included. One SR concluded that laparoscopic techniques take longer than conventional techniques.…”
Section: Effectiveness Of Laparoscopic Cholecystectomymentioning
confidence: 99%